Transcutaneous electrical acupoint stimulation improves endometrial receptivity resulting in improved IVF-ET pregnancy outcomes in older women: a multicenter, randomized, controlled clinical trial - Xiaojun Feng; Na Zhu; Shuo Yang; Li Wang; Wei Sun; Rong Li; Fei Gong; Songping Han; Rong Zhang; Jisheng Han (BMC, 2022)
Abstract Objective To examine the effects and mechanisms of transcutaneous electrical acupoint stimulation (TEAS) on pregnancy outcomes in women undergoing in vitro fertilization (IVF)-embryo transfer (ET). Design, setting, and participants This efficacy study was a multicenter, randomized, controlled clinical trial (RCT) in women receiving IVF-ET. The mechanistic study was a single-center RCT. Interventions The participants received TEAS vs. no TEAS treatment. Main outcome measures In the efficacy study, the primary outcomes were the rates of clinical pregnancy, embryo implantation, and live birth. In the mechanistic study, sex hormones and endometrial protein expression were examined. Results Ultimately, 739 participants were enrolled (367 and 372 in the TEAS and control groups, respectively). The clinical pregnancy rate was higher in the TEAS group than in the controls (55.1% vs. 46.7%, P = 0.03). There were no significant differences in embryo implantation, biochemical pregnancy, and live birth rates between the two groups (all P > 0.05) in the study population. In women > 35 years, the clinical pregnancy rates, embryo implantation rates and live birth rates in the TEAS and control groups were 48.9% vs. 23.7% (P = 0.004),30.8 vs. 13.9% (P = 0.001) and 34.0% vs. 19.7% (P = 0.06) respectively. In the mechanistic study with 120 participants, on the theoretical embryo implantation day, better developed endometrial pinopodes, elevated endometrial integrin α1β1/αVβ3, leukemia inhibitory factor, and elevated serum progesterone levels were found in the TEAS group compared with controls. Conclusion TEAS significantly improved the clinical pregnancy rate in women undergoing IVF-ET, especially in women of older age. It might be due to improved endometrial receptivity. Trial registration ChiCTR-TRC-13003950.